Komunikasi Verbal dan Nonverbal Driver Gojek dalam Membangun Kepercayaan Pelanggan - Alfian Derry Jusup; Satya Candrasari (UNIVERSITAS KALBIS, 2022)
Gojek in this day and age is needed by people to facilitate access to travel and other activities practically, Gojek has a variety of origin drivers so that in serving consumers drivers Gojek has communications that vary from verbal and non-verbal so that the communication of drivers can be conveyed or not delivered, the purpose of research is to find out how verbal and nonverbal communication of the Gojek driver in building customer trust. In this study, researchers used a constructivist paradigm, a qualitative approach and types of descriptive research and collecting interview data, observation and documentation, the results showed that verbal communication that is used by drivers using Indonesian language with polite and relaxed language style to communicate to customers, nonverbal communication in the behavior of the Gojek driver is a face expression message, smell message, gestural message and paralanguage, to build customer trust the driver must provide quality and comfort to the customer, the form of language that is communicated by the driver to his customer will reflect a good or not driver, which will determine the reputation of the Gojek driver.